PSIKIATER DALAM RANAH HUKUM PERADILAN PIDANA - Muhammad Farhan Abdillah; Iman Santoso (Jurnal Komunikasi Hukum, 2022)
The science of criminal law provides a requirement to say that someone committing a crime must fulfill the elements of an act that legally violates the law or has a normative nature against the law, Forensic Psychiatry has a significant position in the field of criminal law as a factor of proof in criminal liability. Psychiatry ensures the size of a person's responsibility in violating criminal law. Often a person in every day seems reasonable in his mind, but in a psychiatric examination it is clear that he has mental problems that reduce his responsibility, but he finds a severe punishment. The purpose of this paper is to determine the role and position of psychiatrists in the criminal justice system. The research method in this paper uses literature research, by applying a qualitative approach this research can be made. Qualitative research is research that interprets a symptom such as a social phenomenon that focuses on the complete picture of a phenomenon to be studied. The results of the discussion show that the role of psychiatrists as legal agents of law enforcement officers and in the criminal justice system is positioned as an expert in every stage of examination in criminal procedural law, both in the investigation stage, additional examination on prosecution and expert testimony on evidence at trial.